COMPARISONAL ANALYSIS OF WATER QUALITY BOARDING WITH FOUR POINTS OF DEPTH (CASE STUDY: DRILL WELL IN FIELD MEDAN AVIATION POLYTECHNIC) - USMAN -; Albert Panjaitan; Sunardi -; Jhony Hidayat; Lisda Juliana Pangaribuan (Universitas Quality, 2022)
This study aims to determine the chemical and physical quality of drilled well water at Medan Aviation Polytechnic. Such as the quality of turbidity, color, Dissolved Solids (TDS), taste, odor, iron (Fe), hardness, nitrate, chromium valence, Lead (Pb), organic matter and pH. This study analyzed the water consumed and compared it with the Regulation of the Minister of Health No. 492/MENKES/PER/IV/2010, covering microbiological, chemical, and physical requirements. The trial results are also compared with the water quality standard values that have been set by the government, PEMENKES No 416/MENKES/PER/IX/1990 concerning Clean Water Quality Requirements. Testing physical and chemical quality of water includes testing elements using a thermometer and testing for color using,sense of sight. The samples used in this study were four samples, namely wells A, B, C and sample D. The drilled well water that has been tested will be used used for daily needs including drinking needs in the cadet dormitories, housing lecturers and employees in campus area. The results showed that turbidity parameter was 2.68 NTU to 4.59 NTU, the color parameter was 4.59 TCU to 5.3 TCU, the TDS parameter was 64.3 to 121.4 mg/l, hardness parameter was 82.32 to 101.9 mg/l, Valence Chromium parameter 0.005 to 0.017 mg/l, Lead parameter 0.02158 to 0.04166 mg/l, Nitrate parameter 1.1 to 1, 5 mg/l, pH parameters 6.9 to 7.2, Fe parameters 0.10581 up to 0.21050 mg/l, organic matter parameters 2.211 to 3.160. So based on the physical parameters and chemical parameters, the borehole water at Medan Aviation Polytechnic meets the requirements set by the government for consumption.